Performance Test of LED Grow Light with Indoor Hydroponic System for Horticultural Plants - Noverdita, Noverdita; Puspitahati, Puspitahati; Triana, Arjuna Neni; Kuncoro, Endo Argo (Fakultas Teknologi Industri Pertanian, 2024)
This study aimed to evaluate the performance of LED grow lights in an indoor hydroponic system for horticultural plants. The problem identified was the need for energy efficiency and optimal yield in hydroponic growth systems. The experimental research method involved collecting descriptive data presented in tables and figures. Variables measured included power consumption, light intensity, temperature, humidity, plant height, leaf count, leaf width, and pH and EC levels. The results showed that lettuce (Lactuca sativa L.) grown with a 25-watt LED grow light in a wick hydroponic system exhibited the best growth compared to lower power levels. The highest productivity was achieved under 12 hours of sunlight, yielding 17.82 tons/ha, while 20 hours of LED lighting resulted in the lowest productivity at 7.11 tons/ha. A 16-hour lighting treatment produced better results, with a yield of 11.05 tons/ha. In conclusion, the duration and type of lighting significantly affect lettuce productivity in a hydroponic system.